2022
DOI: 10.3390/cells11061037
|View full text |Cite
|
Sign up to set email alerts
|

The Atypical Chemerin Receptor GPR1 Displays Different Modes of Interaction with β-Arrestins in Humans and Mice with Important Consequences on Subcellular Localization and Trafficking

Abstract: Atypical chemokine receptors (ACKRs) have emerged as a subfamily of chemokine receptors regulating the local bioavailability of their ligands through scavenging, concentration, or transport. The biological roles of ACKRs in human physiology and diseases are often studied by using transgenic mouse models. However, it is unknown whether mouse and human ACKRs share the same properties. In this study, we compared the properties of the human and mouse atypical chemerin receptor GPR1 and showed that they behave diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
(62 reference statements)
0
7
1
Order By: Relevance
“…The same also applied to the C9 peptide, that showed a higher potency (EC 50 of 1 nM) on GPR1 than on CMKLR1 (24 nM). Based on these results, GPR1 was considered a receptor that preferentially activates the β-arrestin2 pathway (Barnea et al, 2008; Fischer et al, 2021), although other studies showed its ability to mediated G protein signaling as well (De Henau et al, 2016; Degroot et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The same also applied to the C9 peptide, that showed a higher potency (EC 50 of 1 nM) on GPR1 than on CMKLR1 (24 nM). Based on these results, GPR1 was considered a receptor that preferentially activates the β-arrestin2 pathway (Barnea et al, 2008; Fischer et al, 2021), although other studies showed its ability to mediated G protein signaling as well (De Henau et al, 2016; Degroot et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The binding of chemerin to GPR1 results in a weak Ca2+ mobilization and phosphorylation of ERK1/2, but this action participates in the anti-inflammatory response, development of adiposity, hormone secretion, and the regulation of glucose balance in obesity, as well as in the regulation of angiogenesis [ 21 , 22 ]. Both CMKLR1 and GPR1 activation can lead to the recruitment of β-arrestins and receptor internalization [ 23 , 24 ]. GPR1 serves additionally as a scavenger receptor for peptides that cannot stimulate receptor activation.…”
Section: Chemerin Structure and Biological Functionsmentioning
confidence: 99%
“…GPR1 serves additionally as a scavenger receptor for peptides that cannot stimulate receptor activation. Interestingly, GPR1 is not expressed in monocytes, macrophages, or peripheral blood lymphocytes, but instead, it is expressed in cells related to the central nervous system [ 24 , 25 ]. Although chemerin is the only identified ligand for CCRL2, its interaction does not initiate any known signaling pathway; thus, its role remains uncertain; however, it seems to have the ability to amplify local chemerin concentration for CMKLR1 interaction [ 19 , 26 ].…”
Section: Chemerin Structure and Biological Functionsmentioning
confidence: 99%
“…Unlike CMKLR1, the binding of chemerin to GPR1 results in a weak Ca 2+ mobilization and phosphorylation of ERK1/2, and the binding of chemerin to CCRL2 does not signal nor internalize [ 31 ]. Recent findings reported that GPR1 displayed rapid ligand-independent, constitutive internalization and acted as a scavenging receptor with wider ligand specificity [ 34 , 35 ]. These results indicate that CMKLR1 is a typical GPCR for chemerin with canonical G protein-related signaling features, while GPR1 and CCRL2 are atypical GPCRs ( Figure 1 B), and more detailed properties of these receptors are needed for further work.…”
Section: Chemerin Receptorsmentioning
confidence: 99%